2020
DOI: 10.3390/biomedicines8090316
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of STAT5 in Oncogenesis

Abstract: Signal transducer and activator of transcription (STAT) proteins, and in particular STAT3, have been established as heavily implicated in cancer. Recently, the involvement of STAT5 signalling in the pathology of cancer has been shown to be of increasing importance. STAT5 plays a crucial role in the development of the mammary gland and the homeostasis of the immune system. However, in various cancers, aberrant STAT5 signalling promotes the expression of target genes, such as cyclin D, Bcl-2 and MMP-2, that resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 123 publications
0
31
0
Order By: Relevance
“…The most important transcription factor in PRLR signaling is STAT which regulates the growth, differentiation, and survival of mammary tissue. STATs are found to be activated/overexpressed in several types of cancers including breast cancer [ 41 ]. Constitutively activated STAT3 and STAT5, were shown to directly contribute to oncogenesis by stimulating cell proliferation and preventing apoptosis in various cancers.…”
Section: Prlr Signaling Pathwaymentioning
confidence: 99%
“…The most important transcription factor in PRLR signaling is STAT which regulates the growth, differentiation, and survival of mammary tissue. STATs are found to be activated/overexpressed in several types of cancers including breast cancer [ 41 ]. Constitutively activated STAT3 and STAT5, were shown to directly contribute to oncogenesis by stimulating cell proliferation and preventing apoptosis in various cancers.…”
Section: Prlr Signaling Pathwaymentioning
confidence: 99%
“…Although the JAK-STAT pathways are best studied in immune cells to promote cell growth and the immune response, cancer cells can take advantage of the signaling pathway to contribute to malignant phenotypes [ 42 , 43 , 44 ]. STAT3 and STAT5 typically demonstrate tumor promoting activity by inhibiting apoptosis through repression of BAX and BAK transcription, along with induction of BCL2 transcription ( Figure 2 ) [ 45 , 46 , 47 ]. Conversely, JAK1 and STAT1 have been shown to induce apoptosis in a variety of cell models, likely through BCL2 repression and CDKN1A (p21) transcription [ 48 , 49 , 50 , 51 ].…”
Section: Mechanisms Of Trβ-mediated Tumor Suppressionmentioning
confidence: 99%
“…For example, Guignon et al showed that a ligand-binding domain mutant TRβ resulted in enhanced prolactin expression and sustained phosphorylation of STAT5 in a mouse model of breast cancer [ 52 ]. STAT5 is known to inhibit apoptosis and encourage cell cycle progression by promoting BCL2 and CCND1 (cyclin D) transcription, respectively [ 47 , 53 ]. Introduction of wildtype TRβ attenuated prolactin-induced p-STAT5 levels which were further reduced with addition of T 3 .…”
Section: Mechanisms Of Trβ-mediated Tumor Suppressionmentioning
confidence: 99%
“…Although the JAK-STAT pathways are best studied in immune cells to promote cell growth and the immune response, cancer cells can take advantage of the signaling pathway to contribute to malignant phenotypes [45][46][47]. STAT3 and STAT5 typically demonstrate tumor promoting activity by inhibiting apoptosis through repression of BAX and BAK transcription along with induction of BCL2 transcription (Figure 2) [48][49][50]. Conversely, JAK1 and STAT1 have shown to induce apoptosis in a variety of cell models, likely through BCL2 repression and CDKN1A (p21) transcription [51][52][53][54].…”
Section: Trβ Differentially Influences Jak-stat Signalingmentioning
confidence: 99%
“…TRβ has been shown to specifically regulate activity of certain JAK-STAT pairs. For example, Guignon et al showed that TRβ PV/PV in a mouse model of breast cancer resulted in enhanced prolactin expression and sustained phosphorylation of STAT5 [55], which is known to inhibit apoptosis and encourage cell cycle progression by promoting BCL2 and CCND1 (cyclin D) transcription, respectively [50,56].…”
Section: Trβ Differentially Influences Jak-stat Signalingmentioning
confidence: 99%